ANALISIS KEMAMPUAN DASAR TRIGONOMETRI MELALUI SOAL PEMECAHAN MASALAH PADA MAHASISWA UNIVERSITAS NAHDLATUL ULAMA KALIMANTAN BARAT - Assegaf, Syf. Rizekia Zulaikha; Nurdiana, Riyanti; Suriyana, Suriyana (Bestari: Jurnal Pendidikan dan Kebudayaan, 2025)
Abstract: Based on observations in the Trigonometry course, many students still experience difficulties in solving problems related to trigonometric concepts, particularly in the ratios of sine, cosine, and tangent. These difficulties are reflected in the Trigonometry course grades from the previous semester. In addition, during the Geometry course, students also showed confusion in understanding the concepts of sine, cosine, and tangent. The purpose of this study is to describe students’ basic trigonometric abilities in solving problems related to trigonometry. By describing these basic abilities, it is expected that the factors causing students’ previous difficulties can be identified. This study employed a qualitative research method with a descriptive approach. The research sample consisted of one class from the Mathematics Education Study Program, Faculty of Teacher Training and Education, Nahdlatul Ulama University, in the 2025/2026 academic year, comprising four students. Based on the results of the study, it can be concluded that the students’ basic trigonometric ability falls into the low category. This indicates the need for improvements in the learning process, particularly in strengthening students’ understanding of basic trigonometric ratios. Keywords: Trigonometri, basic knowledge   Abstrak: Mata kuliah trigonometri masih banyak mahasiswa yang mengalami kesulitan dalam menyelesaikan soal-soal yang berkaitan dengan trigonometri terutama pada perbandingan sinus, kosinus dan tangen. Kesulitan ini terlihat dari  nilai mata kuliah trigonometri pada semester sebelumnya dan pada mata kuliah geometri pemahaman mahasiswa pada materi sinus, kosinus dan tangen masih banyak mahasiswa yang mengalami kebingungan. Tujuan penelitian ini secara khusus adalah untuk mendeskripsikan kemampuan dasar trigonometri mahasiswa dalam menyelesaikan masalah pada materi trigonometri. Dengan mendeskripsikan kemampuan dasar mahasiswa kita dapat mengetahui faktor-faktor penyebab kesulitan yang dialami mahasiswa sebelumnya. metode penelitian kualitatif dengan pendekatan deskriptif. Dalam penelitian ini peneliti mengambil sampel penelitian yaitu satu kelas prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdlatul Ulama tahun ajaran 2025/2026 yang berjumlah 4 orang. Dari hasil penelitian dapat disimpulkan bahwa kemampuan dasar trigonometri mahasiswa baru masuk kedalam kategori rendah. Kata Kunci:Trigonometri, kemampuan dasar.